2014
DOI: 10.1002/rcs.1629
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygenation measured by near-infrared spectroscopy and jugular vein oxygen saturation during robotic-assisted laparoscopic radical prostatectomy under total intravenous anaesthesia

Abstract: These findings suggested that TIVA could be safely used for RALP. It was also demonstrated that rSO did not accurately reflect SjvO during RALP. Copyright © 2014 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…We did not observe any significant changes in the tissue oxygen saturation while increase in the IAP. This observation is in a good agreement with reports of other authors [23][24][25][26][27][28][29][30][31] where only small changes (increase or decrease) in the saturation were noted. In 3 out of 8 studies no significant changes in StO2 were reported.…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe any significant changes in the tissue oxygen saturation while increase in the IAP. This observation is in a good agreement with reports of other authors [23][24][25][26][27][28][29][30][31] where only small changes (increase or decrease) in the saturation were noted. In 3 out of 8 studies no significant changes in StO2 were reported.…”
Section: Discussionsupporting
confidence: 93%
“…As samples at this level are not contaminated by blood from the external jugular vein, SjvO 2 can accurately reflect the relationship between cerebral oxygen supply and oxygen consumption. 15 The normal baseline value of SjvO 2 is 54% to 75%. 16 Cerebral oxygen supply more than meets cerebral oxygen consumption if its value is more than 75%.…”
Section: Discussionmentioning
confidence: 98%
“…While the data related to the study were recorded by a blinded anesthesia 6 nurse in the anesthesia form, they were also recorded in a separate data collection form. Hypotension was defined as more than 20% decrease in basal MAP [20].…”
Section: Methodsmentioning
confidence: 99%